Dampak Pendapatan Asli Daerah (PAD) dan Pendapatan Transfer Pemerintah Pusat terhadap Belanja Daerah di Jawa Timur Tahun 2018-2022 - Aprillia Arum Anggreini; Diana Zuhroh; Tjandra Wasesa; Wiratna Wiratna; Sutini Sutini (Jurnal Mahasiswa Manajemen dan Akuntansi, 2024)
This study aims to determine how the influence of local revenue (PAD) and Central Government Transfer revenue on regional spending in East Java in 2018-2023 and how much influence partially or simultaneously. The Data used is secondary data obtained from the official website of the Directorate General of financial balance (DGT). Sampling technique using purposive sampling. The number of samples in this study is 117 normally distributed samples. The analysis used is multiple linear regression analysis, by testing classical assumptions first. The R-Square test is used to test the accuracy of the model. As for the hypothesis test using T test (partial) and F test (simultaneous). Based on the results of research that has been done, local revenue (PAD) and Central Government Transfer revenue respectively have a positive and significant effect on regional spending. Simultaneously or jointly local revenue (PAD) and Central Government Transfer revenue significantly affect regional spending.